CHARACTERISATION OF RADIOACTIVE CAESIUM IN SEDIMENTS AT THE NOGAWA RIVER, JAPAN. Issue 13 (9th September 2022) - Inose, Satoshi; Nanri, Yusuke; Saito, Rintaro; Matsuda, Wataru; Honda, Takayuki; Koike, Yuya
Abstract: The TEPCO Fukushima Daiichi Nuclear Power Plant accident that occurred in March 2011 resulted in the release of radioactive caesium into the environment. The radioactive caesium has been detected in the Tama River watershed. Previous investigations have shown that the concentration of radioactive caesium in sediment was relatively high in the Nogawa River. In this study, the relationship between the concentration of radioactive caesium in the sediment and the sediment characteristics was investigated. We found that 137 Cs concentration in the tributary sediment has difficulty migrating downstream, while exhibiting a strong correlation with the amount of organic matter and a correlation with the clay, silt layer. Based on the results, we inferred that 137 Cs is deposited together with the organic matter and clay, silt layer in the sediment and migrates at a slower pace than that in the mainstem.